A SPOT STRUCTURE OF ACCRETION DISK OF U GEMINORUM - Borisov, N. V.; Neustroev, V. V. (Одеські астрономічні публікації, 2017)
On the basis of modelling of emission lines of dwarf novae U Gem, conclusion is made, that the observed orbital phase change of model parameters of a accretion disk can not be explained in frameworks of Keplerian velocity field in a disk. The reason of such change can be spiral shock in a accretion disk.